The world's most prestigious prize : the inside story of the Nobel Peace prize - Lundestad, Geir, 1945- ([Oxford, UK] : Oxford University Press, 2019)
The World's Most Prestigious Prize: The Inside Story of the Nobel Peace Prize is a fascinating, insider account of the Nobel peace prize. Drawing on unprecedented access to the Norwegian Nobel Institute's vast archive, it offers a gripping account of the founding of the prize, as well as its highs and lows, triumphs and disasters, over the last one-hundred-and-twenty years. But more than that, the book also draws on the author's unique insight during his twenty-five years as Director of the Norwegian Nobel Institute and Secretary of the Norwegian Nobel Committee. It reveals the real story of all the laureates of that period - some of them among the most controversial in the history of the prize (Gorbachev, Arafat, Peres and Rabin, Mandela and De Klerk, Obama, and Liu Xiaobo) - and exactly why they came to receive the prize. Despite all that has been written about the Nobel Peace Prize, this is the first-ever account written by a prominent insider in the Nobel system.
The Nobel Peace Prize : past and present -- Alfred Nobel and his will -- The Nobel Peace Prize, 1901-1914 : arbitration -- The Nobel Peace Prize, 1919-1939 : The League of Nations -- The Nobel Peace Prize, 1945-2018 : The United Nations -- Ten portraits, 1990-2012. Mikhael Gorbachev (1990), Aung San Suu Kyi (1991), Nelson Mandela and Frederik Willem de Klerk (1993), Yasser Arafat, Shimon Peres, and Yitzhak Rabin (1994), Kim Dae-jung (2000), The UN and Kofi Annan (2001), Jimmy Carter (2002), Barack H. Obama (2009), Liu Xiabo (2010), The European Union (2012) -- Conclusions.
Print version record.
eBooks on EBSCOhost
Keywords: Nobel Prizes -- History; Peace -- Awards; Peace-building.; Nobel Prize winners -- History; Prix Nobel -- Histoire; Paix -- Prix et récompenses.; Consolidation de la paix; Lauréats du Prix Nobel -- Histoire; REFERENCE -- General; Nobel Prize winners; Nobel Prizes; Peace -- Awards; Peace-building; Electronic books; History